1992
DOI: 10.1111/j.1540-8167.1992.tb01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Sudden Cardiac Death After a First Myocardial Infarction by Pharmacologic or Surgical Antiadrenergic Interventions

Abstract: Introduction: Growing evidence points to sympathetic hyperactivity as one critical trigger for life-threatening arrhythmias among postmyocardial infarction patients.Methods and Results: We have evaluated, in a placebo-controlled multicenter study, the efficacy of a /3-adrenergic blocking agent (oxprenolol 160 mg) and of a selective left cardiac sympathetic denervation in preventing sudden death in patients with a first and anterior myocardial infarction. Two patient groups were studied. The high-risk group inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(79 citation statements)
references
References 51 publications
2
75
1
1
Order By: Relevance
“…The results are based on a strong rationale 21 and match those already observed in other arrhythmogenic conditions. 18,[22][23][24] These findings should therefore have an important impact on the approach to managing CPVT.…”
Section: Discussionmentioning
confidence: 99%
“…The results are based on a strong rationale 21 and match those already observed in other arrhythmogenic conditions. 18,[22][23][24] These findings should therefore have an important impact on the approach to managing CPVT.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Clinically, the only randomized study with LCSD has demonstrated a significant reduction (from 22% to 3.5% during a 21-month follow-up) of SD among high-risk postmyocardial infarction patients. 22 Thus, there is a strong experimental and clinical rationale fostering the expectation that, especially in the setting of augmented sympathetic activity, life-threatening arrhythmias might be prevented or reduced by LCSD.…”
Section: Rationale and Mechanism Of Action Of Lcsdmentioning
confidence: 99%
“…autonomic nervous system; sympathetic nerves; cardiac innervation; neural remodeling REMODELING of the cardiac sympathetic nervous system after myocardial infarction (MI) has been linked to ventricular arrhythmias in animal models (29) and in humans (4,12,24). Modulation of cardiac sympathetic signaling is a major therapeutic strategy to prevent and treat ventricular arrhythmias (1,8,22). Despite its importance, the global electrophysiological consequences of postinfarct neural remodeling from a focal infarct remain poorly characterized.…”
mentioning
confidence: 99%